Carboxymethylchitosan/poly (amidoamine) dendrimer nanoparticles in central nervous systems-regenerative medicine: effects on neuron/glial cell viability and internalization efficiency - Salgado, A. J. (2010)
The applicability of CMCht/PAMAM dendrimer nanoparticles for CNS applications was investigated. AFM and TEM observations revealed that the nanoparticles possessed a nanosphere- like shape with a size from 22.0 to 30.7 nm. The nanoparticles could be bound to fluorescent-probe FITC for tracing purposes. Post-natal hippocampal neurons and cortical glial cells were both able to internalize the FITC-labeled CMCht/PAMAM dendrimer nanoparticles with high efficiency. The percentage of positive cells internalizing the nanoparticles varied, reaching a peak after 48 h of incubation. Further experiments for periods up to 7 d revealed that the periodical addition of FITC-labelled CMCht/ PAMAM dendrimer nanoparticles was needed to maintain the overall percentage of cells internalizing them. Finally, it was also observed that cell viability was not significantly affected by the incubation of dendrimer nanoparticles.